2019
DOI: 10.1097/prs.0000000000005131
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expander Complications Do Not Preclude a Second Successful Implant-Based Breast Reconstruction

Abstract: Background: Implant based breast reconstruction is the most common method of breast reconstruction in the United States but the outcomes of subsequent implant based reconstruction after a tissue expander (TE) complication are rarely studied. The purpose of this study is to determine the long term incidence of implant loss in patents with a previous TE complication. Methods: This is a retrospective review of the long term outcomes of all patients with TE complications at a large academic medical center from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Given the occurrence of complication after initial expander placement, it is important for surgeons and patients to consider the options available for a safe continuation of reconstruction. In the instance of implant infection, the reported cause of the majority of implant failure in previously published work and our data, 8,10 the decision between medical management, reoperation with implant salvage, or implant removal must be made.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Given the occurrence of complication after initial expander placement, it is important for surgeons and patients to consider the options available for a safe continuation of reconstruction. In the instance of implant infection, the reported cause of the majority of implant failure in previously published work and our data, 8,10 the decision between medical management, reoperation with implant salvage, or implant removal must be made.…”
Section: Discussionmentioning
confidence: 79%
“…Of the 56 patients in the study's patient cohort who underwent explantation of the implant, the majority underwent a secondary implant-based reconstruction successfully. A recent study by Poppler et al 10 further demonstrated the safety of a secondary implant-based reconstruction after initial tissueexpander failure, with 79% of their patient cohort having successful reconstruction at the time of final follow-up despite earlier explantation. In our patient cohort, 674 patients were initially screened, and the 60 patients who underwent tissue-expander explantation were included.…”
Section: Discussionmentioning
confidence: 96%
“…Implant loss is likely to become a major problem worldwide as rates of implant‐based breast reconstruction continue to increase. The growing magnitude of the problem is reflected in the numbers of recent studies reporting the clinical outcomes of autologous or further implant‐based reconstruction performed after a failed implant‐based procedure. Although the technical success rates of further reconstructive surgery are high, few studies have included patient‐reported outcomes (PROs) in their assessment of success.…”
Section: Discussionmentioning
confidence: 99%
“…Since time to postoperative complications requiring in-patient admission for intravenous antibiotics or operative removal is generally within 60 days of reconstruction, the risk of hardware exposure in this acute time period may be worth mitigating with a subpectoral technique. 29 Even though recent data demonstrate no significant difference in postoperative complication and infection rate, it may be prudent for plastic surgeons less familiar with prepectoral placement or encountering any concern regarding mastectomy skin flap thickness to utilize the subpectoral technique. [30][31][32] The greater postoperative pain involved with the subpectoral technique may be treated with pectoral type-2 (PECS II) nerve blocks or paravertebral blocks to allow for same day discharge.…”
Section: Oncologic Reconstructionmentioning
confidence: 99%